Pelaksanaan Perlindungan Hukum Merek Untuk Pengusaha Kerajinan Sulaman Karawo Di Gorontalo - Tomu, Yayan Hanapi (Gorontalo Law Review, 2018)
the use of Trademarks and the importance of legal protection Trademarks for karawo entrepreneurs vary and also depend on their type or field of business, whether: workshop owners or batik production houses, shop owners or karawo showrooms, or owners of both. However, the average respondent stated that the main factor to attract consumers is the quality and motif or karaoke design. The average respondent also does not want to imitate the trademark of another employer, and understands that registration of the trademark rights can strengthen the protection of the use of his trademark. There does not appear to be a problem in relation to the use of Trademarks for batik products. Because there is almost no Brand dispute case among kerajanian businessmen karawo. Then, the wishes of the karawo entrepreneurs to use and register a Collective Brand are varied, but on average respondents consider that the karawo products they produce have regional characteristics.